(untitled) (Revista Cocar, 2012)
O estudo procura mostrar como evoluiu a educação na Amazônia nos últimos 60 anos. Passando da economia extrativista em que as raras escolas da região ofereciam para a maior parte dos poucos habitantes que estudavam, apenas o curso primário de 4 anos, e entendia as habilidades de ler, escrever e contar como sendo as necessidades básicas do cidadão. Enfoca o modelo educacional adotado durante a ditadura, o processo de urbanização, a explosão das massas em busca de vagas nas escolas nos anos 70/80 e; e também o surgimento ele um fosso entre escola pública e privada. Aponta conquistas na educação pela sociedade, mas também as desigualdades regionais que persistiram e estão expressas claramente nos indicadores de educação da região face às outras regiões brasileiras. Analisa a gradativa percepção, pela sociedade, da educação como um precioso capital humano e como um dever do Estado. E como a sociedade compreendeu que o indivíduo que não consegue usufruir do direito a uma educação de boa qualidade está sendo condenado à exclusão social, à desigualdade e à pobreza. Palavras-Chave: Educação. Sociedade. Amazônia. Education and society in the Amazon in more than a halph of a century The studyaims at showing how the education in the Amazon has evolved throughout over the last 60 years. Its development has ranged from an exploitation economy, in which a scarce number of schools did offer for the great majority of a few inhabitants who studied, solely the four-years elementary stage and understood the abilities of reading, writing and counting as basic necessities of a citizen. It focuses on the educational model adopted during the military dictatorship, the urbanization process, the big boom towards the "search for enrollment opportunities in the schools during the 70s and 80s decades; and also the abyss formed between the private and public schools. It points out both the advances in education accomplished by the society and the regional inequalities which "persisted and are clearly expressed in the educacional statistics and figures of the region, contrasted to the other Brazilian regions. The study also analyzes the societyâ€™s gradual reasoning of the education not only as a precious human capital but also as a State duty. Another relevant aspect depicted is how the society has realized that the individual who is unable to benefit from a" good education is sentenced to social exclusion, inequality and poverty. Keywords: Education. Society. Amazon.